2008
DOI: 10.1159/000166547
|View full text |Cite
|
Sign up to set email alerts
|

Application of Autologous Cryopreserved Bone Marrow Mesenchymal Stem Cells for Periodontal Regeneration in Dogs

Abstract: Background: Stem cell-based therapies have shown great promise in regenerative medicine and continue to generate wide interest in future clinical applications. However, the issue of storage and preservation of stem cells, for future clinical applications, still requires extensive investigation. Objective: The purpose of this study was to evaluate the effect of cryopreservation on the regenerative capacity of bone marrow stem cells in periodontal defects in dogs. Materi als and Methods: Bone marrow mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 38 publications
1
76
0
2
Order By: Relevance
“…When combined with GTR membrane, Steiner et al (2007) found that periosteum transplanted to furcation defects could help the regeneration of alveolar bone, cementum and periodontal ligament. Similar results were reported in the application of the periodontal ligament fibroblasts and BMSCs by Yan et al (2005), Hovey et al (2006), Gay et al (2007) and Li et al (2009). Although the multiple differentiation potential of periosteum cells has been shown, no study has confirmed that periosteum cells can differentiate to cementoblasts.…”
Section: Discussionsupporting
confidence: 81%
“…When combined with GTR membrane, Steiner et al (2007) found that periosteum transplanted to furcation defects could help the regeneration of alveolar bone, cementum and periodontal ligament. Similar results were reported in the application of the periodontal ligament fibroblasts and BMSCs by Yan et al (2005), Hovey et al (2006), Gay et al (2007) and Li et al (2009). Although the multiple differentiation potential of periosteum cells has been shown, no study has confirmed that periosteum cells can differentiate to cementoblasts.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the scaffold must be able to maintain a space within the wound site for the cells to grow into (5). Although using soft scaffolds such as hydro gels or collagen sponge has been the predominant strategy (8,20,29,42,54,64), the applications of these soft scaffolds are limited due to their poor mechanical properties. Solid scaffolds such as hydroxyapatite/tricalcium phosphate (HA/TCP) provide improved support for periodontal tissue regeneration (7,33).…”
Section: Discussionmentioning
confidence: 99%
“…For periodontal tissue engineering, sufficient supply of autologous cells is of paramount importance for the preparation of transplants. In animal experiments, periodontal ligament fibroblasts (PDLCs) (Zhang et al 2007;Lin et al 2008) and bone marrow stroma cell (BMSCs) (Hasegawa et al 2006;Li et al 2008) have been two main cell sources for periodontal tissue engineering. Recent studies have showed that grafted periosteum or periosteum-derived cells (PDCs) could enhance periodontal wound healing, and they promote alveolar bone repair, as well as facilitate periodontal membrane and cementum regeneration (Steiner et al 2007;Mizuno et al 2006).…”
Section: Instructionmentioning
confidence: 99%